Urgency of Performance Tiering for Indonesia's Supreme Court: A Constitutional Law Perspective - Agus Digdo Nugroho; Nikko Banta Meliala (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
The Supreme Court of Indonesia is pivotal as a representative of judicial power. However, evaluations and reports indicate suboptimal performance outcomes, necessitating the implementation of a structured performance tiering framework. This research employs an empirical juridical approach involving surveys, court visits, and focus group discussions, supplemented by a literature review. The study highlights the Supreme Court's need to operationalize its vision of